Quantitative Evaluation on Electric Motor Thermal Image for Comparison Hot Spot and Measuring Point Regions - Wa Ode Siti Nur Alam; Sahabuddin Hay; St Nawal Jaya (Universitas Sriwijaya, 2018)
Inspection of the condition on industrial equipment becomes an urgent matter for industry. Infrared thermography inspection provides enormous benefits in preventive and predictive maintenance routines, especially for critical electrical equipment to prevent sudden damage to the equipment when the production process is underway, insofar that it impacts on the process. The result of inspection is in the form of thermal image which depicts the temperature of the electrical equipment. In general, thermal image evaluation is still analyzed manually by relying on visual reading by technicians. This would allow for errors in evaluating the image. Thus, this study used thermal images as the results of electric motor inspections, which are in hot spot and measuring point regions. Furthermore, this study aims to quantify the overheating resulted in electric motor by comparing those two regions using color entropy by Graphical User Interface (GUI) MATLAB. The study stages comprised of: zooming and object (region) cropping on color thermal image, color image histogram, calculating of color entropy (red, green, blue), and calculating of the color entropy average. The result of study on ten electric motor thermal images showed that the color entropy is higher in the measuring point region than the color entropy in the hot spot region. The average of color entropy in hot spot region were in the range of 2.9497 – 3.9578 and measuring point region were in the range of 5.1182 – 5.4489.